2000
DOI: 10.1089/107662900419393
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Penicillin Resistance BetweenNeisseriaein Microcosm

Abstract: Horizontal gene transfer between commensal and pathogenic Neisseriae is the mechanism proposed to explain how pathogenic species acquire altered portions of the penA gene, which encodes penicillin binding protein 2. These changes resulted in a moderately penicillin-resistant phenotype in the meningococci, whose frequency of isolation in Spain increased at the end of the 1980s. Little has been published about the possibility of this gene transfer in nature or about its simulation in the laboratory. We designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It has long been believed that horizontal exchange of genetic material among Neisseria is responsible for the mosaic nature of both virulence factors and housekeeping genes such as penA (Spratt et al ., 1992; Bowler et al ., 1994), aroE and glnA (Zhou et al ., 1997). In support of this hypothesis, in vitro co‐cultivation studies have provided evidence that such genetic exchange is feasible in nature (Frosch and Meyer, 1992; Bowler et al ., 1994; Orus and Vinas, 2000). A basic requirement for this type of DNA transfer to occur in vivo is the co‐colonization of the nasopharynx with different neisserial strains, serogroups and commensals.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been believed that horizontal exchange of genetic material among Neisseria is responsible for the mosaic nature of both virulence factors and housekeeping genes such as penA (Spratt et al ., 1992; Bowler et al ., 1994), aroE and glnA (Zhou et al ., 1997). In support of this hypothesis, in vitro co‐cultivation studies have provided evidence that such genetic exchange is feasible in nature (Frosch and Meyer, 1992; Bowler et al ., 1994; Orus and Vinas, 2000). A basic requirement for this type of DNA transfer to occur in vivo is the co‐colonization of the nasopharynx with different neisserial strains, serogroups and commensals.…”
Section: Discussionmentioning
confidence: 99%
“…Other members of this genus, such as N. lactamica, N. sicca, N. flavescens, and various others, do not cause disease but can colonize the human nasopharynx and have been involved in antibiotic resistance transfer to N. meningitidis (21,28). Linz and coworkers have established that commensal neisseriae and N. meningitidis frequently exchange chromosomal DNA (17), consistent with the notion of a shared neisserial global gene pool (18).…”
mentioning
confidence: 84%
“…Surprisingly, no C:2bP.1.5 strain isolated in the examined period was PenI, unlike isolates with the same phenotype detected in other European countries [23] or in previous years in Italy. Interestingly, it has long been suggested that the exogenous DNA in the penA gene is responsible for the decreased affinity of PBP2 and, consequently, for higher MICs of penicillin [24].…”
Section: Meningococcal Disease Remains a Dreadful Infection Even Inmentioning
confidence: 99%